BRD7 Promotes Cell Proliferation and Tumor Growth Through Stabilization of c-Myc in Colorectal Cancer - Zhao, Ran; Liu, Yukun; Wu, Chunchun; Li, Mengna; Wei, Yanmei; Niu, Weihong; Yang, Jing; Fan, Songqing; Xie, Yong; Li, Hui; Wang, Wei; Zeng, Zhaoyang; et al. (Frontiers in Cell and Developmental Biology, 2021)
BRD7 functions as a crucial tumor suppressor in numerous malignancies. However, the effects of BRD7 on colorectal cancer (CRC) progression are still unknown. Here, based on the BRD7 knockout (BRD7-/-) and BRD7 WT (BRD7+/+) mouse models constructed in our previous work, we established an AOM/DSS-induced mouse model. BRD7+/+ mice were found to be highly susceptible to AOM/DSS-induced colitis-associated colorectal cancer, and BRD7 significantly promoted cell proliferation and cell cycle G1/S transition, but showed no significant effect on cell apoptosis. Furthermore, BRD7 interacted with c-Myc and stabilized c-Myc by inhibiting its ubiquitin proteasome-dependent degradation. Moreover, restoring the expression of c-Myc in BRD7 silenced CRC cells restored cell proliferation, cell cycle progression and tumor growth in vitro and in vivo. In addition, BRD7 and c-Myc were both significantly upregulated in CRC patients, and high expression of these proteins was associated with clinical stage and poor prognosis in CRC patients. Collectively, BRD7 functions as an oncogene and promotes CRC progression by regulating the ubiquitin proteasome-dependent stabilization of c-Myc protein. Targeting the BRD7/c-Myc axis could be a potential therapeutic strategy for colorectal cancer.